Análisis del uso de bins y portabins en cosecha mecanizada de palto hass “Persea americana” Valle Chao parte alta – La Libertad - Solar Espejo, Carlos Enrique (2019)
In the present investigation, two hass avocado harvesting procedures were evaluated, both the traditional one that is a harvest in javas which for the picking of the harvested avocado is used a wagon implement that is hooked to the pulling of the tractor, and the mechanized harvest that It is a harvest in bins that uses a portabin attachment that is also hooked to the tractor's hydraulic system and draft. I analyzed the two procedures in order to compare the total cost of each procedure and find the difference between the efficiency of each one, taking as a measurement parameter the average cost of dollars per ton transported, which covers the hours of machinery and the amount of labor costs of personal stowage, all this in order to demonstrate that the mechanized harvesting process in bins is more effective and economical than the traditional harvest in jacks. Before the analysis of the cabinet, 33 data were taken from the data history of the 2017 campaign comparing it with the data obtained in the 2018 campaign, recording as data the tons produced daily in which it is identified if its harvest was in jabas or bin, the total hours of machinery considering the total sum of hours of the tractors used in the day without taking into account the downtime since all the tractors have a GPS installed with which we monitor only the effective hours, and finally the amount of manpower stowage used in the two harvesting procedures.